Efeitos do exercício físico sobre a histomorfometria óssea e cartilaginosa de ratas ooforectomizadas submetidas à imobilização - Simas, José Martim Marques (2015)
The aim of this study was to analyze the effects of the physical exercise of climbing stairs in bone and cartilage histomorphometric parameters in rats submitted to a model of osteoporosis and immobilization. 36 Wistar rats were separated into six groups were used: G1, G2 and G3 groups were subjected to pseudo-oophorectomy; and G4, G5 and G6 to oophorectomy. After surgery, all groups remained 60-day rest and the rats G2, G3, G5 and G6 had the right hind limb (MPD) immobilized during 15 days, followed by remobilization same period, being free in the box to G2 and G5, and climb stairs in G3 and G6. At the end of the experiment, the rats were euthanized, their tibias removed bilaterally and submitted to histological routine. Morphometric analysis showed that there was a statistically significant decrease in area (p = 0.0178) and cortical thickness (p = 0.0024), thickness of articular cartilage (p = 0.0138) and epiphyseal plate were made (p = 0.0187), and the number of osteocytes (p <0.0001) and chondrocytes (p = 0.0006) as well as significant increase in the medullary canal (p = 0.0384) in immobilized limbs of ovariectomized rats. However, the stair climbing exercise was able to reverse the loss of bone cortex (area (F (5; 29) = 6.24, p = 0.0007) and thickness (F (5; 29) = 4.11 p = 0.0062)), cartilage (articular cartilage thickness (F (5; 29) = 13.88, p <0.0001) and epiphyseal plate (F (5; 29) = 14.72, p <0.0001)) and cellular (osteocytes (F (5; 29) = 14.55, p <0.0001) and chondrocytes (F (5; 29) = 10.16, p <0.0001)) resulting of oophorectomy associated with immobilization. It was also observed a significant decrease in trabecular thickness and area in the members subjected to immobilization, however, both as the free remobilization and climb stairs were able to recover from this loss. Morphological analysis of tibia articular cartilage, no changes in cell structure or organization of the rats not subjected to immobilization (G1 and G4) were verified by observing only considerable decrease in the thickness and number of chondrocytes in G4 (oophorectomized group) . In female rats that were free remobilization (G2 and G5), it was observed degeneration regions of articular cartilage with subchondral bone exposure, loss of cellular organization, discontinuity of tidemark, the presence of fissures and flocculation, as well as decreased number of chondrocytes. On the other hand, G2 female rats (pseudo-oophorectomized group, immobilized and free remobilization) showed some regions of granulation tissue (pannus). In rats subjected to exercise climb stairs (G3 and G6), there were repair signs of cartilaginous structures, the presence of clones and pannus. In G6 (oophorectomized group, remobilization and immobilized ladder), although it was observed subcortical invasion of blood vessels in the calcified zone, and increasing the amount of isogenous groups and the thickness of the calcified zone. From the results obtained in this study, it can be concluded that climbing stairs exercise was effective in the recovery process of bone and cartilage tissue damaged by immobilization on osteoporosis model by ovariectomy in rats.